What goes up does not always come down: patterns of distress, physical and psychosocial morbidity in people with cancer over a one year period. Issue 1 (4th October 2011) - Carlson, Linda E.; Waller, Amy; Groff, Shannon L.; Giese‐Davis, Janine; Bultz, Barry D.
Abstract Background As the concept of distress as the 6th vital sign gains strength in cancer care, research on the experience of patients is critical. This study longitudinally examined patients' physical and psychosocial concerns over the year following diagnosis. Methods Between July 2007 and February 2008, patients attending a large tertiary cancer centre were recruited to participate in a study examining their levels of distress, pain, fatigue, depression and anxiety over a year. Results A total of 877 patients provided baseline data with 620, 589 and 505 retained at 3, 6 and 12 months, respectively. Overall, levels of distress, depression and anxiety decreased significantly over the study period. No significant changes were found in levels of pain or fatigue. Demographics (being unmarried) and medical interventions (particularly having radiation therapy) predicted persistent distress, anxiety and depression, whereas receiving psychosocial support predicted decreased levels of distress, anxiety and depression. Some patients reported continued clinical levels of distress (29%), pain (19%) and fatigue (40%) 12 months post diagnosis. Discussion For some people, distress, depression, and anxiety may be transient and decrease over time, but for others they may be sustained. Pain and fatigue may remain present in many cancer patients. There is a need to modify current clinical practice to facilitate the appropriate assessment and management of distress. Copyright © 2011 John Wiley & Sons, Ltd.